Non-AIDS-defining comorbidities impact health related quality of life among older adults living with HIV - Zhabokritsky, Alice; Klein, Marina; Loutfy, Mona; Guaraldi, Giovanni; Andany, Nisha; Guillemi, Silvia; Falutz, Julian; Arbess, Gordon; Tan, Darrell H. S.; Walmsley, Sharon (Frontiers in Medicine, 2024)
The life expectancy of people living with HIV receiving effective combination antiretroviral therapy is approaching that of the general population and non-AIDS-defining age-related comorbidities are becoming of greater concern. In order to support healthy aging of this population, we set out to explore the association between multimorbidity (defined as presence of 2 or more non-AIDS-defining comorbidities) and QoL. We performed a cross-sectional analysis using data from the Correlates of Healthy Aging in Geriatric HIV (CHANGE HIV) study, a Canadian cohort of people living with HIV age 65 years and older. Study participants completed two QoL modules, the general QoL and health related QoL (HR-QoL). 433 participants were included in the analysis with a median age of 69 years (interquartile range, IQR 67-72). The median number of comorbidities among study participants was 3 (IQR 2-4), with 78% meeting the definition of multimorbidity. General QoL scores (median 66, IQR 58-76) were lower than HR-QoL scores (median 71, IQR 61-83) and were not associated with multimorbidity after adjusting for age, sex, relationship status, household income, exercise, tobacco smoking history, malnutrition, time since HIV diagnosis, and HIV-related stigma. In contrast, multimorbidity was associated with lower HR-QoL (adjusted =-4.57, 95% CI -8.86, -0.28) after accounting for the same variables. Several social vulnerabilities (not having a partner, low household income), health behaviours (lower engagement in exercise, smoking), and HIV-related factors (HIV stigma, longer time since HIV diagnosis) were also associated with lower QoL. Overall, our study demonstrated a high burden of multimorbidity among older adults living with HIV in Canada, which has a negative impact on HR-QoL. Interventions aimed at preventing and managing non-AIDS-defining comorbidities should be assessed in people living with HIV to determine whether this can improve their HR-QoL.